Qualitative study investigating the underlying motivations of healthy participants in phase I clinical trials - Manton, Kerry J (BMJ Open, 2019)
OBJECTIVES: If patients are to reap the benefits of continued drug development, an understanding of why healthy participants take part in phase I clinical trials is imperative. The current study aimed to explore the nature of these underlying motivations which may, in turn, improve the overall participant experience and assist in the development of more effective recruitment and retention strategies. DESIGN: This study used a qualitative design based on the theory of planned behaviour. Specifically, it explored healthy participants’ underlying behavioural, control and normative beliefs which influence their participation in phase I clinical trials. SETTING: This study took place at a company that specialises in conducting phase I and phase II clinical trials in the Australian state of Queensland. PARTICIPANTS: Participants (n=31) were either currently undergoing a phase I clinical trial or had previously taken part in a phase I clinical trial. RESULTS: Results showed that the motivations were varied and not solely centred on financial gains. Reported advantages of participation included altruism, while inconvenience was most often reported as a disadvantage. Friends were reported as those most likely to approve, while one’s mother was reported as most likely to disapprove. Having a suitable time frame/flexible scheduling and feeling comfortable taking part in the trial were both the most commonly reported facilitators, while inflexible scheduling/time commitment was the most commonly reported barrier. CONCLUSIONS: Practical implications included the need for organisations involved in clinical trials to be mindful of inflexible scheduling and exploring the possibility of making educational materials available to family members who may be concerned about the risks associated with participation. Overall, it is anticipated that the results of this study will improve the understanding of factors that influence phase I clinical trial participation which may, ultimately, help develop new therapeutics to improve patient health.